2023
DOI: 10.1177/00333549221132534
|View full text |Cite
|
Sign up to set email alerts
|

How Governor Directives Changed Health Workforce Flexibility in Response to the COVID-19 Pandemic

Abstract: Objectives: In times of heightened population health needs, the health workforce must respond quickly and efficiently, especially at the state level. We examined state governors’ executive orders related to 2 key health workforce flexibility issues, scope of practice (SOP) and licensing, in response to the COVID-19 pandemic. Methods: We conducted an in-depth document review of state governors’ executive orders introduced in 2020 in all 50 states and the District of Columbia. We conducted a thematic content ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Health leaders around the world implemented strategies to bolster the capacity of the health workforce to respond to the acute phase of the pandemic. [5][6][7][8] The increased volume and acuity of patients, in tandem with an increase in health worker absences, required multiple types of health workforce strategies. A rapid scoping review of workforce strategies employed during previous health emergencies revealed scarce evaluative evidence to inform health system leaders' efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health leaders around the world implemented strategies to bolster the capacity of the health workforce to respond to the acute phase of the pandemic. [5][6][7][8] The increased volume and acuity of patients, in tandem with an increase in health worker absences, required multiple types of health workforce strategies. A rapid scoping review of workforce strategies employed during previous health emergencies revealed scarce evaluative evidence to inform health system leaders' efforts.…”
Section: Introductionmentioning
confidence: 99%
“…What we actually experienced was not one single acute peak in healthcare demand, but wave upon wave of COVID‐19 surge, and the cumulation of layers of chronic impacts. Health leaders around the world implemented strategies to bolster the capacity of the health workforce to respond to the acute phase of the pandemic 5–8 . The increased volume and acuity of patients, in tandem with an increase in health worker absences, required multiple types of health workforce strategies.…”
Section: Introductionmentioning
confidence: 99%